2021
DOI: 10.1007/s40194-021-01204-1
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical properties of wire and arc additively manufactured high-strength steel structures

Abstract: Additive manufacturing with steel opens up new possibilities for the construction sector. Especially direct energy deposition processes like DED-arc, also known as wire arc additive manufacturing (WAAM), is capable of manufacturing large structures with a high degree of geometric freedom, which makes the process suitable for the manufacturing of force flow-optimized steel nodes and spaceframes. By the use of high strength steel, the manufacturing times can be reduced since less material needs to be deposited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
(25 reference statements)
1
19
0
Order By: Relevance
“…From a cooling time of approx. 25 s, the ultimate tensile strength of the WAAM wire remained more or less constant up to 45 s. This was in accordance with studies of other authors, who focused on testing of mechanical properties in tensile specimens of an actual WAAM component/wall [14], in which, however, a relatively high effect of the cooling conditions on the yield strength was found. In future investigations, testing of the yield strength should therefore be mandatory.…”
Section: Thermophysical Welding and Forming Simulation With Dilatometersupporting
confidence: 91%
See 2 more Smart Citations
“…From a cooling time of approx. 25 s, the ultimate tensile strength of the WAAM wire remained more or less constant up to 45 s. This was in accordance with studies of other authors, who focused on testing of mechanical properties in tensile specimens of an actual WAAM component/wall [14], in which, however, a relatively high effect of the cooling conditions on the yield strength was found. In future investigations, testing of the yield strength should therefore be mandatory.…”
Section: Thermophysical Welding and Forming Simulation With Dilatometersupporting
confidence: 91%
“…In addition, studies demonstrated the suitability and efficiency of the controlled MSG short arc (e.g., cold metal transfer (CMT) or ColdArc) for large components [11]. Different studies dealt with the strong dependence of the temperature distribution and the resulting component geometry on the welding parameters [12][13][14]. These investigations showed the great importance of heat control in setting the desired microstructural properties of high-strength steels using WAAM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to the nominal values provided by the manufactures, the applied building parmeters caused lower values resulting from the interpass temperature applied. A full overview on tensile properties was published earlier [35].…”
Section: Specimen Manufacturingmentioning
confidence: 99%
“…The weld metal microstructure of all four specimens was comparable and mainly composed of upper and lower bainite. A detailed analysis of this feed material and its mechanical parameters can be found elsewhere [35].…”
Section: Metallographic Characterizationmentioning
confidence: 99%